The role of ferroptosis in diabetic cardiovascular diseases and the intervention of active ingredients of traditional Chinese medicine - Zhang, Xiaobing; Sun, Jing; Wang, Jianying; Meng, Tianwei; Yang, Jianfei; Zhou, Yabin (Frontiers in Pharmacology, 2023)
Cardiovascular diseases (CVDs), encompassing ischaemic heart disease, cardiomyopathy, and heart failure, among others, are the most prevalent complications of diabetes and the leading cause of mortality in patients with diabetes. Cell death modalities, including apoptosis, necroptosis, and pyroptosis, have been demonstrated to be involved in the pathogenesis of CVDs. As research progresses, accumulating evidence also suggests the involvement of ferroptosis, a novel form of cell death, in the pathogenesis of CVDs. Ferroptosis, characterised by iron-dependent lipid peroxidation, which culminates in membrane rupture, may present new therapeutic targets for diabetes-related cardiovascular complications. Current treatments for CVDs, such as antihypertensive, anticoagulant, lipid-lowering, and plaque-stabilising drugs, may cause severe side effects with long-term use. Traditional Chinese medicine, with its broad range of activities and minimal side effects, is widely used in China. Numerous studies have shown that active components of Chinese medicine, such as alkaloids, polyphenols, and saponins, can prevent CVDs by regulating ferroptosis. This review summarises the recent findings on the regulatory mechanisms of active components of Chinese medicine against ferroptosis in CVDs, aiming to provide new directions and a scientific basis for targeting ferroptosis for the prevention and treatment of diabetic CVDs.